PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI AKADEMIK SMA IBRAHIMY 2 SUKOREJO MENGGUNAKAN METODE TOGAF - Nadia Selvi Ramadhani; Ummul Khoirun Fitriyah; Akhlis Munazilin (Jurnal Riset Teknik Komputer, 2025)
The implementation of digital technology in academic activities has become an urgent necessity for educational institutions to improve service quality, enhance information management efficiency, and support accurate decision-making. SMA Ibrahimy 2 Sukorejo faces challenges in the form of fragmented processes, the use of non-integrated applications, and limited infrastructure and data management. This research aims to develop an enterprise architecture blueprint for an integrated Academic Information System using the TOGAF Architecture Development Method (ADM). The research method employed is qualitative–design oriented, with data collected through observation, in-depth interviews, document analysis, and validation through discussions with relevant stakeholders within the school. The design stages follow the ADM framework, including the development of the Architecture Vision, Business Architecture, Application Architecture, Data Architecture, and Technology Architecture, complemented by gap analysis and the formulation of an implementation roadmap. The results indicate that the current academic processes lack adequate integration of data and applications, highlighting the need for an architectural framework to serve as a foundation for digital transformation at the school. The resulting architecture blueprint includes business capability mapping, key academic process flows, a list of integrated applications, a conceptual data model, and a hybrid cloud-based technology infrastructure design. The gap analysis identifies major deficiencies in workflow, information management, and infrastructure, while the implementation roadmap is structured into five stages, ranging from system foundation development to core module implementation, integration, and advanced analytics. Through this blueprint, the school gains strategic and technical guidance for developing a structured, standards-compliant, and sustainable Academic Information System. This architecture blueprint is expected to support improvements in operational efficiency, information transparency, and the quality of educational services, as well as serve as a reference for future research and architectural design in similar educational institutions.